Development of digital literacy of students with disabilities (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2021)
The article is devoted to the formation of digital literacy in teaching children with disabilities on the basis of two components: digital user component, digital correction-intellectual component, which are developed by the authors. Discussed the importance of the state program "Digital Kazakhstan" and one of these areas of human capital. Described by the authors created a course on computer science aimed at improving the digital literacy of students with disabilities. The main research methods are the theoretical analysis of educational and methodological, scientific literature and Internet content on digital literacy, and components of digital literacy, generalization of practical experience in the formation and development of digital literacy of students with disabilities. The content of digital literacy of students with disabilities was investigated, the thematic content of the educational sections of the course on the formation and development of digital literacy was substantiated, corresponding to the main components of digital literacy: digital user component, digital correction-intellectual component.
Keywords: education, digital literacy, computer science, students with disabilities, components of digital literacy.